2020
DOI: 10.1259/bjr.20190878
|View full text |Cite
|
Sign up to set email alerts
|

Establishing local diagnostic reference levels for common orthopaedic procedures using the mini C-arm fluoroscope

Abstract: Objective: Mini C-arm fluoroscopes are widely used by orthopaedic surgeons for intraoperative image guidance without the need for radiographers. This puts the responsibility for radiation exposure firmly with the operating surgeon. In order to maintain safe and best practice under U.K. Ionising Radiation (Medical Exposure) Regulations, one must limit radiation exposure and audit performance using national diagnostic reference levels (DRLs). In the case of the mini C-arm, there are no national DRLs. IR(ME)R, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In this study, we demonstrated that the overall amount of radiation seen by patients during hand and wrist fracture fixation is low, with a median DAP of 4.8 cGycm 2 , median ED of 0.13 μSv, and median exposure time of 43 seconds. This is in line with Kropelnicki et al, 14 who looked at 1664 extremity procedures requiring the mini c-arm and measured median DAP to be 2.98 cGycm 2 for hand, 5.18 cGycm 2 for wrist, 2.78 cGycm 2 for forearm, 8.71 cGycm 2 for elbow, and 3.71 cGycm 2 for foot and ankle procedures. Madhvani et al 15 reported median DAP values of 2.73 cGycm 2 for wrist ORIF, 1.05 cGycm 2 for phalangeal ORIF, and 2.36 cGycm 2 for all CRPPs.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we demonstrated that the overall amount of radiation seen by patients during hand and wrist fracture fixation is low, with a median DAP of 4.8 cGycm 2 , median ED of 0.13 μSv, and median exposure time of 43 seconds. This is in line with Kropelnicki et al, 14 who looked at 1664 extremity procedures requiring the mini c-arm and measured median DAP to be 2.98 cGycm 2 for hand, 5.18 cGycm 2 for wrist, 2.78 cGycm 2 for forearm, 8.71 cGycm 2 for elbow, and 3.71 cGycm 2 for foot and ankle procedures. Madhvani et al 15 reported median DAP values of 2.73 cGycm 2 for wrist ORIF, 1.05 cGycm 2 for phalangeal ORIF, and 2.36 cGycm 2 for all CRPPs.…”
Section: Discussionsupporting
confidence: 86%
“…Local DRLs have been used in the last years to report patient dose indicators with small samples (e.g., in paediatrics) [ 7 ], according to body metrics (7), after installing X-rays systems with new imaging technology, or when national DRLs are still not available for some clinical indications [ 9 12 ].…”
Section: How To Establish Local Drlsmentioning
confidence: 99%
“…Local DRLs have been used in the last years to report patient dose indicators with small samples (e.g., in paediatrics) [7], according to body metrics (7), after installing X-rays systems with new imaging technology, or when national DRLs are still not available for some clinical indications [9][10][11][12]. The PiDRL project [6] recommends establishing local DRLs for emerging or increasing new practices, such as hybrid imaging when the CT is used for diagnostic purposes and paediatric cone-beam CT (CBCT) examinations.…”
Section: How To Establish Local Drlsmentioning
confidence: 99%